Climate Change, Global Food Security, and the U.S. Food System - Brown, M.E.; Antle, J.M.; Backlund, P.; Carr, E.R.; Easterling, W.E.; M.K. Walsh; Ammann, C.; Attavanich, W.; Barrett, C.B.; M.F. Bellemare; Dancheck, V.; Funk, C.; et al. (United States Department of Agriculture, 2015)
Food security—the ability to obtain and use sufficient amounts of safe and nutritious food—is a fundamental human need. Achieving food security for all people everywhere is a widely agreed upon international objective, most recently codified in the United Nations Sustainable Development Goals for 2030. This report describes the potential effects of climate change on global food security and examines the implications of these effects for the United States.